High‐frequency stimulation of the subthalamic nucleus modulates neuronal activity in the lateral habenula nucleus. (13th October 2016) - Hartung, Henrike; Tan, Sonny K. H.; Temel, Yasin; Sharp, Trevor
Abstract: High‐frequency stimulation (HFS) of the subthalamic nucleus (STN) is often used to treat movement disability in advanced Parkinson's disease, but some patients experience debilitating psychiatric effects including depression. Interestingly, HFS of the STN modulates 5‐HT neurons in the dorsal raphe nucleus (DRN) which are linked to depression, but the neural substrate of this effect is unknown. Here, we tested the effect of STN stimulation on neuronal activity in the lateral habenula nucleus (LHb), an important source of input to DRN 5‐HT neurons and also a key controller of emotive behaviours. LHb neurons were monitored in anaesthetized rats using single‐unit extracellular recording, and localization within the LHb was confirmed by juxtacellular labelling. HFS of the STN (130 Hz) evoked rapid changes in the firing rate of the majority of LHb neurons tested (38 of 68). Some LHb neurons (19/68) were activated by HFS, while others (19/68), distinguished by a higher basal firing rate, were inhibited. LHb neurons that project to the DRN were identified using antidromic activation and collision testing ( n = 17 neurons). Some of these neurons (5/17) were also excited by HFS of the STN, and others (7/17) were inhibited although this was only a statistical trend. In summary, HFS of the STN modulated the firing of LHb neurons, including those projecting to the DRN. The data identify that the STN impacts on the LHb‐DRN pathway. Moreover, this pathway may be part of the circuitry mediating the psychiatric effects of STN stimulation experienced by patients with Parkinson's disease. Abstract : Stimulation of the subthalamic nucleus (STN) treats movement disability in Parkinson's patients, but can produce psychiatric effects. Here, we show that STN stimulation alters neuronal activity in the lateral habenula nucleus, a source of input to midbrain 5‐HT neurons and a key controller of emotional responses. Thus, potential circuitry mediating the psychiatric effects of STN stimulation is revealed.